Bussiness mathematics - Lau, Too Kya; Phang, Yook Ngor; Wee, Kok Kiang (SJ Learning, 2022)
Business Mathematics is specially written for first and second year students at Universiti Teknologi MARA who are pursuing diploma courses in business studies, banking, investment analysis, public administration, tourism management, culinary arts, office management and business administration. This book is also suitable for students following the off-campus courses and distance learning programs.